Analysis of transverse corner cracks from continuous casting process and comparison to laboratory experiments. Issue 1 (31st December 2022) - Gontijo, M.; Hoflehner, C.; Ilie, S.; Six, J.; Sommitsch, C.
Abstract: Low alloyed steel slabs produced by continuous casting can present transverse corner cracks, which are critical due to the oxide layer formed within the crack. Understanding this type of failure and reproducibility of the phenomenon through laboratory tests is of great value for dealing with this problem. The present work analyzed samples from slab corners, where cracks were identified. The fracture surfaces were examined using a scanning electron microscope (SEM) and cut to have their microstructure analyzed with a light optical microscope (LOM). Using etching to reveal the microstructure of the samples from the slabs, it was seen that the cracks were initiated and propagated at the prior austenite grain boundaries. Furthermore, the SEM images from the corner samples were compared to those from the physical simulation of the continuous casting process from previous work, and the structure found was like the ones tested at critical temperatures. The same was noted for the microstructure analysis, where cracks were also seen to follow the grain boundaries. Therefore, it was concluded that the behavior resulted from the laboratory tests performed with in-situ melted samples with the BETA 250-5 machine were in good accordance with the reality of the continuous casting process.